A BRIEF BIBLIOMETRIC SURVEY ON THE SURVIVAL OF SMALL AND MEDIUM ENTERPRISES (SMEs) DURING ECONOMIC CRISIS - Noraida Saidi; Nik Zam Nik Wan; Syuhaila Razak; Suzana San; Azilawati Abdullah@Abd Aziz; Siti Nor Adawiah Hussin, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
COVID-19 pandemic which have shaken the world in 2019 has changed people’s lives and the conduct of business. It has given a tremendous impact to the health sector as well as the business sector. In Malaysia, SMEs were most badly impacted by the pandemic, where more than 32,000 SMEs had to close their operations. Besides, COVID-19 also had dramatically slowed national growth to -6% by 2020. Thus, the objective of this study is to present a bibliometric analysis of publications from the Scopus database on the survival of SMEs to cope with the impact of economic crisis due to COVID-19. A bibliometric approach has been employed in this study to analyze the published studies on the survival of SMEs from 1998 to 2023. The journal articles are acquired from Scopus’ website. This study has collected and examined 201 relevant articles. This study has discovered the trend of publication from 1998 to 2023. Besides, this study illustrates that Sustainability Switzerland was the top journal with a total of 10 publications and South Africa was the highest producers of publications with 28 publications. Besides, the most cited articles are Naidoo V. (2010) with a total of 285 citations. Co-citation analysis of cited sources, co-occurrence of authors’ keywords and Network analysis of co-authorship countries were analyzed using VOSviewer. The study's findings could assist the policymakers in making suitable initiatives to improve SME’s sustainability in Malaysia. The research also gives insights for current and potential businesses on the available survival strategies to cope with economic crisis.